The child healthcare system in Azerbaijan - Avaz, Namazova Adelia (Turk Pediatri Ars, 2020)
The evolution of the child healthcare system in Azerbaijan is described herein. In particular, the article describes the development of child healthcare in the country, with particular focus on the Soviet and post-Soviet period. The organisation of healthcare (treatment and prophylaxis) for the general population, women and children in particular, and the current developing projects and programs are discussed. Finally, the article reports the current major priorities for child healthcare in Azerbaijan.